FACE BLANCHE, BOUCHE MUETTE, CORPS TOURMENTÉ : « PIERROT L’INVISIBLE » DANS LES REPRÉSENTATIONS DÉCADENTES (White face, silent mouth, troubled body. “Invisible Pierrot” in decadent depictions) - Eva Voldřichová Beránková (Ostium, 2015)
Conceived in the 16th century as one of the zannis (clownish valets) of the commedia dell’arte, Pierrot becomes a frequent theme of decadent literary works and paintings. The fin de siècle period is fascinated by this androgyne creature endowed with a floured face and an undefined body covered with a wide piece of clothing. Most of the contemporary creators perceive Pierrot as a perfect personification of the decadent spirit. Our study seeks to demonstrate the development of this character in several decadent novels, stories, poems, plays, pantomimes and paintings. What does the invisible man hide? What aspirations and anxieties of French society does he reveal? And why had his interpretations changed so radically at the beginning of the 20th century?